SENSORY ACCEPTANCE OF BELEDANG FISH COOKIES - Yenni Okfrianti; Rosita Pebrianti; Risda Yulianti (Poltekkes Kemenkes Bengkulu, 2023)
The low level of per capita fish consumption among Indonesian communities is attributed to two factors linked to weak supply and low demand. Beledang fish or Cutlass fish (Trichiurus lepturus) is one type of sea fish with high nutritional value but low consumer appeal. This study aims to determine the sensory acceptability of Beledang fish cookies. The materials required for this cookies manufacturing comprised Beledang fish flour, wheat flour, margarine, butter, fine sugar, eggs, lemon, skim milk, cornstarch, baking powder, and palm sugar. A completely randomized design (CRD) was employed for this study, with different proportions: 40%, 50%, and 60% of Beledang fish. The production of Beledang fish flour involves several steps. Firstly, 1000 grams of Beledang fish is cleaned by removing the gills and washed with flowing water. Subsequently, the fish is steamed for 10 minutes. Afterward, the fish meat is separated from the bones and dried using an oven at a temperature of 50oC for 5 h. The dried fish meat is finely ground and sifted through a mesh with a size of 60. From 1000 grams of raw Beledang fish, approximately 130 grams of flour is obtained. The organoleptic tests showed the most preferred colour, taste, texture, and aroma for cookies were found in the formulation with a 60% of Beledang fish. There were significant differences between organoleptic properties of the cookies at 40%, 50%, and 60% Beledang fish cookies (p<0.05).